The Effectiveness of Social Media and Service Quality in Influencing the Decision to Visit a Tourist Village - Bagus Setiawan; Ria Astina; Cindi Pramita (Sean Institute, 2026)
The development of digital technology has encouraged the use of social media as a primary promotional tool in the tourism sector, including the development of tourist villages. In addition to social media, service quality is also a crucial factor in creating memorable tourism experiences and influencing tourists' decisions to visit. This study aims to analyze the effectiveness of social media and service quality in influencing tourists' decisions to visit tourist villages. This research used a qualitative, descriptive approach. Data were obtained through in-depth interviews, observation, and documentation with informants including tourist village managers, tourists, and local communities. Data analysis was conducted using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that social media plays a significant role in shaping tourists' initial perceptions and interest in visiting through visual content, easy access to information, and online reviews from visitors. Meanwhile, service quality, demonstrated by the friendliness of managers and local communities, responsiveness of service, and the comfort of facilities, significantly influences tourist satisfaction during their visit. Tourists' decision to visit is the result of a multi-step process, with social media playing a dominant role in the pre-visit phase, while service quality plays a significant role in the direct experience and post-visit phase. This study concludes that social media and service quality complement each other in influencing tourists' decision to visit tourist villages. Therefore, tourist village managers are advised to consistently optimize the use of social media and continuously improve service quality to attract, satisfy, and retain tourists.